Boosting Visible-Light-Driven Hydrogen Evolution Enabled by Iodine-Linked Magnetically Curved Graphene with Mobius-like Electronic Paths - Liangjun Cai; Hongxia Liu; Xiaoxiao Yan (Molecules)
Materials with high electron transfer performance remain a key focus in photocatalytic research, as they can effectively promote the separation of photogenerated carriers and enhance the utilization efficiency of photogenerated electrons. To enhance the effective utilization of photogenerated electrons, the MSIG material was prepared by incorporating the iodine clusters and magnetic Fe3O4 into the as-synthesized crumpled graphene oxide (CGO) to construct Möbius-like electronic transmission pathways. The introduction of magnetic groups optimized the spin orientation of electrons, facilitating directional electron transport and thereby enhancing the photocatalytic efficiency of the material. Experimental results reveal that, in visible light-driven hydrogen production reactions, the eosin Y (EY)-sensitized Pt-Fe3O4-MSIG catalyst exhibits outstanding catalytic performance, with a hydrogen production rate of 1.48 mL/h, which is 15 times higher than that of the Pt-Fe3O4 catalyst. Photoelectrochemical analyses show a significant increase in the catalyst’s fluorescence lifetime, attributed to the Möbius strip-like electron transport channels within the material. Theoretical calculations further support this by demonstrating that the bandgap widening of the CGO reduces the recombination probability of photogenerated carriers, thereby improving their average lifetime. This study offers a novel approach for the design of visible-light-driven photocatalytic materials.